Pädiatrische epileptische Enzephalopathien mit Manifestation oberhalb des Neugeborenenalters: ein Up-date - Trollmann, Regina; Borggräfe, Ingo; Müller-Felber, Wolfgang; Brandl, Ulrich (Klinische Neurophysiologie, 2021)
Developmental and epileptic encephalopathies represent complex and neurodegenerative disorders characterized by onset of refractory seizures usually in the first year of life and associated with motor and intellectual disability. The new ILAE classification of seizures and epilepsies proposed a revised definition of epileptic encephalopathies including electro-clinical phenotype as well as etiological spectrum and associated comorbidities. Modern genetic techniques led to the identification of a precise genotype in several electro-clinical syndromes such as West syndrome and Dravet syndrome. EEG continues to play a specific role as an additional tool in diagnosis and management of epileptic encephalopathies with special focus on the diagnosis of complications such as subclinical seizures and status epilepticus as well as treatment monitoring. This article reviews current aspects of complex pediatric epileptic encephalopathies and the significance of EEG monitoring.
CRIS-Team Scopus Importer:2021-09-24
Keywords: CSWS; Dravet syndrome; Landau-Kleffner syndrome; Lennox-Gastaut syndrome; West syndrome